Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Find reliable answers to your questions from a wide community of knowledgeable experts on our user-friendly Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Sure! Let's solve the equation [tex]\(-4x + (-3) = -x + 3\)[/tex] using algebra tiles step by step.
1. Add 4 positive [tex]\(x\)[/tex]-tiles to both sides and create zero pairs:
Initially, we have:
[tex]\[ -4x + (-3) \quad = \quad -x + 3 \][/tex]
By adding 4 positive [tex]\(x\)[/tex]-tiles to both sides of the equation, we get:
[tex]\[ -4x + 4x + (-3) \quad = \quad -x + 4x + 3 \][/tex]
This simplifies to:
[tex]\[ 0 + (-3) \quad = \quad 3x + 3 \][/tex]
Which is simply:
[tex]\[ -3 \quad = \quad 3x + 3 \][/tex]
2. Add 3 negative unit tiles to both sides and create zero pairs:
Now we have:
[tex]\[ -3 \quad = \quad 3x + 3 \][/tex]
By adding 3 negative unit tiles to both sides of the equation, we get:
[tex]\[ -3 + (-3) \quad = \quad 3x + 3 + (-3) \][/tex]
This simplifies to:
[tex]\[ -6 \quad = \quad 3x \][/tex]
3. Divide the unit tiles evenly among the [tex]\(x\)[/tex]-tiles:
Now we have:
[tex]\[ -6 \quad = \quad 3x \][/tex]
To isolate [tex]\(x\)[/tex], we divide both sides by the coefficient of [tex]\(x\)[/tex], which is 3:
[tex]\[ -6 \div 3 \quad = \quad 3x \div 3 \][/tex]
This results in:
[tex]\[ -2 \quad = \quad x \][/tex]
Thus, the solution to the equation [tex]\(-4x + (-3) = -x + 3\)[/tex] is:
[tex]\[ \boxed{-2} \][/tex]
1. Add 4 positive [tex]\(x\)[/tex]-tiles to both sides and create zero pairs:
Initially, we have:
[tex]\[ -4x + (-3) \quad = \quad -x + 3 \][/tex]
By adding 4 positive [tex]\(x\)[/tex]-tiles to both sides of the equation, we get:
[tex]\[ -4x + 4x + (-3) \quad = \quad -x + 4x + 3 \][/tex]
This simplifies to:
[tex]\[ 0 + (-3) \quad = \quad 3x + 3 \][/tex]
Which is simply:
[tex]\[ -3 \quad = \quad 3x + 3 \][/tex]
2. Add 3 negative unit tiles to both sides and create zero pairs:
Now we have:
[tex]\[ -3 \quad = \quad 3x + 3 \][/tex]
By adding 3 negative unit tiles to both sides of the equation, we get:
[tex]\[ -3 + (-3) \quad = \quad 3x + 3 + (-3) \][/tex]
This simplifies to:
[tex]\[ -6 \quad = \quad 3x \][/tex]
3. Divide the unit tiles evenly among the [tex]\(x\)[/tex]-tiles:
Now we have:
[tex]\[ -6 \quad = \quad 3x \][/tex]
To isolate [tex]\(x\)[/tex], we divide both sides by the coefficient of [tex]\(x\)[/tex], which is 3:
[tex]\[ -6 \div 3 \quad = \quad 3x \div 3 \][/tex]
This results in:
[tex]\[ -2 \quad = \quad x \][/tex]
Thus, the solution to the equation [tex]\(-4x + (-3) = -x + 3\)[/tex] is:
[tex]\[ \boxed{-2} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.